GOING CONCERN COMPANY AND ITS RELATION TO SUSTAINABILITY REPORT DISCLOSURE: EVIDENCE FROM SOEs IN INDONESIA - Saktiana Rizki Endiramurti; Achmad Budiman Rosadi; Agung Nur Probohudono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
This study refers to the issue that is happening in Indonesian State-Owned Enterprises (SOEs), especially in the case of going concern. The purpose is to provide empirical evidence about the relationship between going concern companies and corporate characteristics on the disclosure of sustainability report. The sample used is a non-financial SOEs company in Indonesia, consisting of 54 companies during the period 2014-2016. This study employs regression analysis of panel data with statistical tool Eviews version 9.0. The results support three out of four research hypotheses, in which going concern audit opinion and firm characteristics assessed through firm size and age had significant influence on sustainability report disclosure. This indicates that the larger and longer the company stands, the company will present the sustainability reporting more fully. The more complete presentation of sustainability reporting becomes one of the important factors for the auditor in determining going concern opinion in its report.